The influence of art therapy media usage on guidance and counseling services in children of primary school - Nenden Nurrohmah (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
Primary school-aged children are the development of middle and late childhood. The period in which children can verbalize emotional conflict experienced. But in elementary school-aged children, found children who have difficulty in verbalize feelings and understand emotions. To achieve the successful implementation of guidance and counseling services in primary schools, a media is needed to help the implementation of guidance and counseling services in terms of digging information on children who have difficulty in understanding emotions, such as the use of art therapy media. Art therapy is used as a tool in the implementation of guidance and counseling services. So children can express thoughts and feelings they can not express, such as physical violence or complex emotional experiences. Implementation of guidance and counseling services can be assisted by using art therapy media as a tool to dig information in children who have difficulty in verbalize feelings and understand emotions.